A heat-resistant and antibacterial AS composite material and preparation method thereof

By using styrene-maleic anhydride-acrylonitrile copolymer as a compatibility agent in AS composite materials, combined with the solubility of silver ion and the setting of carrier, the problems of discoloration and insufficient antibacterial performance of AS composite materials during high-temperature processing are solved, and efficient antibacterial effect and excellent mechanical properties are achieved.

CN116333441BActive Publication Date: 2025-03-07ZHUZHOU TIMES ENG PLASTICS TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211469008.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-03-07
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

Existing AS composite materials are prone to discoloration during high temperature processing, and have insufficient antibacterial properties, making it difficult to meet the requirements of strong antibacterial plastics.

Method used

Styrene-maleic anhydride-acrylonitrile copolymer is used as the compatibility agent, and the silver ion solubility is set to 1-2%, zirconium phosphate is used as the carrier of silver ions, and alkali-free chopped glass fibers and appropriate additives are selected, and granulated through a special screw combination of twin-screw extruder.

Benefits of technology

The AS composite material stays at 270°C for 5 minutes without discoloration, maintains excellent mechanical properties, and reaches an antibacterial rate of ≥99%, meeting the requirements of strong antibacterial plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a heat-resistant antibacterial AS composite material, which is prepared from the following raw materials in parts by weight: 66.4-88.8 parts by weight of AS, 10-30 parts by weight of glass fiber, 0.4-0.8 parts by weight of a compatibilizer, 0.4-0.8 parts by weight of an inorganic silver antibacterial agent, and 0.3-2 parts by weight of an auxiliary agent, wherein the compatibilizer is a styrene-maleic anhydride-acrylonitrile copolymer, and the anhydride content of the compatibilizer is 14%-20%. The AS composite material prepared by the present invention has an antibacterial rate of more than 99% against Escherichia coli and Staphylococcus aureus, and the AS composite material does not change color and has excellent mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermoplastic polymer materials, and in particular relates to a temperature-resistant and antibacterial AS composite material and a preparation method thereof. Background Art

[0002] Acrylonitrile-styrene (AS) resin is a thermoplastic with excellent performance, good molding and mechanical properties, good dimensional stability, low molding shrinkage, and is widely used in the field of household appliances, such as axial flow fan blades, cross-flow fan blades and centrifugal fan blades in air conditioners. With the emergence of infectious viruses such as SARS, SARS, and coronavirus, people have paid more attention to health issues, and antibacterial materials and their products have become more and more popular in the market. At present, industrial standards have been formulated for the antibacterial properties of household appliance plastic products. Plastics with an antibacterial rate of ≥99% can be used as strong antibacterial plastics, and plastics with an antibacterial rate of ≥90% can be used as plastics with antibacterial effects.

[0003] As a widely used composite material, glass fiber reinforced AS can reduce the growth of bacteria in corresponding products by adding antimicrobial agents. Common antimicrobial agents include natural antimicrobial agents, organic antimicrobial agents and inorganic antimicrobial agents. Natural antimicrobial agents cannot be commercialized on a large scale due to poor heat resistance and processing difficulties. Organic antimicrobial agents use organic acids, phenols, quaternary ammonium salts, benzimidazoles and other antimicrobial ingredients, which also have disadvantages such as poor heat resistance, short life and easy decomposition. Inorganic antimicrobial agents mainly include photocatalyst antimicrobial agents and inorganic metal ion antimicrobial agents. Among them, photocatalyst antimicrobial agents need to be illuminated by light of appropriate wavelengths to produce better antimicrobial effects, which have great limitations. The widely used inorganic metal antimicrobial agents have high sterilization rates and strong broad spectrum, among which inorganic silver antimicrobial agents have the best effect.

[0004] However, due to the high reactivity of silver ions, they are easy to react with many components in many material systems, resulting in easy discoloration during processing, especially in the injection molding process of air-conditioning cross-flow fan blade products. Due to the thinness of the product, a higher temperature injection molding (such as 270°C) is often required. In addition, the material stays in the screw for a long time. After a period of continuous injection molding, the product often has obvious color difference before and after, resulting in an increase in product defective rate. In response to this situation, the usual solution is to use silver-based antibacterial agents as the main antibacterial agent, and to match other types of antibacterial agents, or to directly replace them with other non-silver antibacterial agents. Chinese invention patent CN105742094A uses a photocatalyst antibacterial agent and an inorganic silver antibacterial agent as an antibacterial agent, and provides an antibacterial AS composition and a preparation method thereof; Chinese invention patent CN105504567A uses a photocatalyst type and a zinc oxide whisker compound component as an antibacterial agent, and provides an antibacterial glass fiber reinforced AS composition. Although the above patent solves the problem of high temperature discoloration to a certain extent, it also sacrifices some antibacterial properties and is difficult to meet the requirement that the antibacterial rate of strong antibacterial plastics should be ≥ 99%.

[0005] Chinese invention patent CN111500013A adopts a compound system of inorganic antibacterial agent and organic mildew inhibitor, and provides an antibacterial and mildew-proof reinforced ABS composite material for wind blades and its preparation method. The antibacterial rate of the composite material is ≥99%. However, since this scheme uses ABS as the base resin and adds a large amount of SMA containing highly reactive groups and organic mildew inhibitor components with poor thermal stability, not only the material strength is low, but also the risk of discoloration during processing and use is greatly increased, and the high temperature resistance is poor. Summary of the invention

[0006] In order to overcome the technical problems of poor antibacterial performance of AS composite materials in the prior art and easy discoloration during high-temperature processing, the present invention provides a temperature-resistant and antibacterial AS composite material and a preparation method thereof. The prepared AS composite material has an antibacterial rate of more than 99% against Escherichia coli and Staphylococcus aureus, and the AS composite material does not change color and has excellent mechanical strength.

[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0008] The first aspect of the present invention provides a temperature-resistant and antibacterial AS composite material, wherein the composite material is prepared from the following raw materials in parts by weight:

[0009]

[0010] The compatibilizer is a styrene-maleic anhydride-acrylonitrile copolymer, and the anhydride content of the compatibilizer is 14% to 20%.

[0011] The compatibilizer in the present application can form an interface layer between the glass fiber and the AS resin, and the interface layer can transfer stress, thereby enhancing the bonding strength between the glass fiber and the resin and improving the mechanical properties of the material. Under normal circumstances, in order to ensure the bonding effect of the two-phase interface, the amount of the compatibilizer added is generally relatively high, and in the present application, styrene-maleic anhydride-acrylonitrile copolymer is selected as the compatibilizer. In order to reduce the probability of discoloration due to collision reaction with silver ions, the amount used is only 0.4 to 0.8 parts by weight, and the anhydride content in the styrene-maleic anhydride-acrylonitrile copolymer is limited to 14% to 20%, which can not only improve the interfacial bonding between the AS resin and the glass fiber and improve the mechanical properties of the material, but also reduce the reactivity of the compatibilizer, so that the prepared composite material is not easy to discolor.

[0012] As an optional embodiment, in the AS composite material provided by the present invention, the solubility of silver ions in the inorganic silver antibacterial agent is 1-2%, and the carrier of the silver ions is zirconium phosphate.

[0013] The silver ion solubility is set to 1-2%, which ensures that the composite material has excellent antibacterial effect, reduces the probability of silver ions contacting and reacting with other systems, and reduces the occurrence of high-temperature reaction discoloration. At the same time, due to the strong adsorption capacity of zirconium phosphate for silver ions, zirconium phosphate is used as a carrier to prevent silver ions from precipitating and becoming free in the system, further reducing the occurrence of high-temperature discoloration reactions.

[0014] As an optional embodiment, in the AS composite material provided by the present invention, the glass fiber is an alkali-free chopped glass fiber, the single fiber diameter of the glass fiber is 7 μm to 14 μm, and the fiber length is 3 mm to 4.5 mm.

[0015] In the present application, alkali-free chopped glass fibers are selected, and the single filament diameter is set to 7 μm to 14 μm, and the fiber length is set to 3 mm to 4.5 mm, so that the prepared composite material can have better mechanical properties.

[0016] As an optional embodiment, in the AS composite material provided by the present invention, the auxiliary agent is one or more of an antioxidant, a lubricant, and a pigment.

[0017] As an optional embodiment, in the AS composite material provided by the present invention, the antioxidant is one or more of a phenolic antioxidant or a phosphite antioxidant, and specifically may be BASF's 1010 or 168.

[0018] As an optional embodiment, in the AS composite material provided by the present invention, the lubricant is ethylene bisstearamide or stearate.

[0019] The lubricant in the present application can improve the dispersion of the antibacterial agent, reduce the shear heat during processing, and further reduce the discoloration of the material. Specifically, it can be EB-FF from Kao of Japan and PETS from Lonza of the United States.

[0020] As an optional embodiment, in the AS composite material provided by the present invention, the pigment is a common inorganic pigment, such as zinc sulfide, carbon black, etc., which are combined in a certain proportion, and the main function is to give the material a certain color.

[0021] As an optional embodiment, in the AS composite material provided by the present invention, the preparation method of the styrene-maleic anhydride-acrylonitrile copolymer is as follows: maleic anhydride, styrene, and acrylonitrile are stirred in weight percentage (10-20%): (70-85%): (5-10%) to form a solution, and the solution is slowly added dropwise to styrene with a weight percentage of 20-25%, and the polymerization reaction is carried out in a normal pressure reactor at a temperature of 100-110° C. for 8.5-9.5 hours to obtain a styrene-maleic anhydride-acrylonitrile copolymer.

[0022] The second aspect of the present invention provides a method for preparing the above-mentioned temperature-resistant and antibacterial AS composite material, wherein AS, glass fiber, compatibilizer, inorganic silver antibacterial agent and auxiliary agent are transported to a twin-screw extruder for granulation according to the mass ratio, wherein the screw combination of the twin-screw extruder includes 3 to 5 groups of shear blocks, each group of shear blocks has 1 to 2 blocks, and the angle of the shear block is one or more of 30°, 45° or 60°.

[0023] In the present invention, 3 to 5 groups of shear blocks are set, and the angle of each shear block is 30°, 45° or 60°. Different shear block angles have different shear dispersion effects. Generally, the larger the angle, the smaller the shear effect and the better the dispersion effect. By setting shear blocks at different angles, the present application can enhance the dispersion of antibacterial agents and compatibilizers, reduce the probability of silver ions contacting and reacting with other systems, and reduce the occurrence of high temperature reaction discoloration.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The AS composite material prepared in the present invention breaks through the conventional method of adding a large amount of compatibilizer (generally 2-10%), and only a very small amount of compatibilizer can improve the interface state between the glass fiber and the resin. Styrene-maleic anhydride-acrylonitrile copolymer is selected as the compatibilizer, and its anhydride content is limited to 14%-20%. This can not only improve the interface adhesion between the AS resin and the glass fiber and improve the mechanical properties of the material, but also reduce the reactivity of the compatibilizer, so that the prepared composite material is not easy to change color.

[0026] (2) In the process of preparing the composite material, the present invention provides a special screw assembly to enhance dispersion, reduce the probability of silver ions contacting and reacting with other components of the system, and reduce the occurrence of high-temperature reaction discoloration.

[0027] (3) The AS composite material prepared by the present invention has an antibacterial rate of ≥99% while maintaining excellent mechanical properties, and the material does not change color when kept at 270°C for 5 minutes, and has excellent heat resistance. DETAILED DESCRIPTION

[0028] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in combination with the specification and preferred embodiments, but the protection scope of the present invention is not limited to the following specific embodiments.

[0029] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0031] AS resin was selected from NF3400 of Ningbo Formosa Chemical Industry Co., Ltd., glass fiber was selected from ECS13-4.5-T439 of Taishan Fiberglass Co., Ltd., silane coupling agent was selected from KH 792 of Nanjing Aocheng Co., Ltd., antibacterial agent was selected from JDHKP-003 of Jinda Nano, antioxidant was selected from BASF 1010 and 168 (1:1), lubricant was selected from PETS of Lonza Co., Ltd., and gray pigment was a mixture of zinc sulfide and inorganic carbon black in a weight ratio of 200:1.

[0032] Example 1

[0033] (1) Preparation of compatibilizer: 62 g of maleic anhydride, 500 g of styrene and 30 g of acrylonitrile were stirred at room temperature to form a solution, which was slowly added dropwise to 120 g of styrene. After polymerization was carried out in a reactor at a temperature of 100° C. and a pressure of normal pressure for 9 hours, the copolymer was separated for use to obtain a styrene-maleic anhydride-acrylonitrile copolymer with an anhydride content of 14.6%.

[0034] (2) Preparation of AS composite material: Take 88.68 parts of AS, 0.4 parts of compatibilizer, 10 parts of glass fiber, 0.4 parts of antibacterial agent, 0.2 parts of antioxidant, 0.3 parts of lubricant, and 0.8 parts of gray pigment. The materials are fully mixed and melt-extruded and granulated through a twin-screw extruder. The melt extrusion processing conditions of the twin-screw extruder are: extrusion temperature 190℃-240℃, main engine speed 350rpm, and the aspect ratio of the extruder is 35:1. The screw assembly is composed of 3 groups of shear blocks, of which the number of shear blocks is 6, and the shear blocks are 30° and 45° in 1 group. A heat-resistant and antibacterial AS composite is prepared.

[0035] Example 2

[0036] (1) Preparation of compatibilizer: 85 g of maleic anhydride, 500 g of styrene and 43 g of acrylonitrile were stirred at room temperature to form a solution, which was slowly added dropwise to 120 g of styrene. After polymerization for 8.5 h in a reactor at 105° C. and normal pressure, the copolymer was separated for use to obtain a styrene-maleic anhydride-acrylonitrile copolymer having an anhydride content of 16.8%.

[0037] (2) Preparation of AS composite material: Take 78.28 parts of AS, 0.6 parts of compatibilizer, 20 parts of glass fiber, 0.6 parts of antibacterial agent, 0.2 parts of antioxidant, 0.3 parts of lubricant, and 0.8 parts of gray pigment. The materials are fully mixed and melt-extruded and granulated through a twin-screw extruder. The melt-extrusion processing conditions of the twin-screw extruder are: extrusion temperature 190℃-240℃, main engine speed 350rpm, and the aspect ratio of the extruder is 35:1. The screw assembly is 4 groups of shear blocks, of which the number of shear blocks is 8 in total, and the shear blocks are 45° and 60° in one group to prepare a heat-resistant and antibacterial AS composite.

[0038] Example 3

[0039] (1) Preparation of compatibilizer: 120 g of maleic anhydride, 500 g of styrene and 60 g of acrylonitrile were stirred at room temperature to form a solution, which was slowly added dropwise to 120 g of styrene. After polymerization for 9.5 h in a reactor at 95° C. and normal pressure, the copolymer was separated for use to obtain a styrene-maleic anhydride-acrylonitrile copolymer with an anhydride content of 19.2%.

[0040] (2) Preparation of AS composite material: Take 67.88 parts of AS, 0.8 parts of compatibilizer, 30 parts of glass fiber, 0.8 parts of antibacterial agent, 0.2 parts of antioxidant, 0.3 parts of lubricant, and 0.8 parts of gray pigment. The materials are fully mixed and melt-extruded and granulated through a twin-screw extruder. The melt-extrusion processing conditions of the twin-screw extruder are as follows: extrusion temperature 190℃-240℃, main engine speed 350rpm, and the aspect ratio of the extruder is 35:1. The screw assembly is composed of 5 groups of shear blocks, of which there are 9 shear blocks in total, 4 groups of shear blocks at 45° and 60°, and 1 group of 45° alone, to prepare a heat-resistant and antibacterial AS composite.

[0041] Comparative Example 1

[0042] A heat-resistant and antibacterial AS composition is prepared from the following raw materials in parts by weight: 84.08 parts of AS, 5 parts of compatibilizer prepared in Example 1, 10 parts of glass fiber, 0.4 parts of antibacterial agent, 0.2 parts of antioxidant, 0.3 parts of lubricant, and 0.8 parts of gray pigment. The materials are fully mixed and melt-extruded and granulated through a twin-screw extruder. The melt-extrusion processing conditions of the twin-screw extruder are as follows: extrusion temperature 190°C-240°C, main engine speed 350rpm, and aspect ratio of the extruder 35:1. The screw assembly has 3 groups of shear blocks, wherein the number of shear blocks is 6 in total, and the shear blocks are 30° and 45° in one group.

[0043] Comparative Example 2

[0044] A heat-resistant and antibacterial AS composition is prepared from the following raw materials in parts by weight: 78.38 parts of AS, 0.5 parts of coupling agent, 20 parts of glass fiber, 0.6 parts of antibacterial agent, 0.2 parts of antioxidant, 0.3 parts of lubricant, and 0.8 parts of gray pigment. The materials are fully mixed and melt-extruded and granulated through a twin-screw extruder. The melt-extrusion processing conditions of the twin-screw extruder are as follows: extrusion temperature 190°C-240°C, main engine speed 350rpm, and length-to-diameter ratio of the extruder 35:1. The screw assembly has 4 groups of shear blocks, of which the number of shear blocks is 8 in total, and the shear blocks are grouped into 45° and 60°.

[0045] Comparative Example 3

[0046] A heat-resistant and antibacterial AS composition is prepared from the following raw materials in parts by weight: 67.88 parts of AS, 0.8 parts of compatibilizer prepared in Example 3, 30 parts of glass fiber, 0.8 parts of antibacterial agent, 0.2 parts of antioxidant, 0.3 parts of lubricant, and 0.8 parts of gray pigment. The materials are fully mixed and melt-extruded and granulated through a twin-screw extruder. The melt-extrusion processing conditions of the twin-screw extruder are as follows: extrusion temperature 190°C-240°C, main engine speed 350rpm, and aspect ratio of the extruder 35:1. 7 groups of shear blocks, of which the number of shear blocks is 13 in total, 6 groups of shear blocks 45° and 60°, and 1 group of 45° alone.

[0047] Performance Testing

[0048] The antibacterial performance was tested according to GB / T31402-2015 "Test Method for Antibacterial Performance of Plastic Surfaces". The temperature discoloration resistance was tested on a Donghua injection molding machine at 90T and 270°C. The material stayed for 5 minutes and the plate was made. 10 molds were made and the color of the color plate was visually observed. The test results are shown in Table 1:

[0049] Table 1: Test data of composite materials prepared in Examples 1-3 and Comparative Examples 1-3

[0050]

[0051] From the performance test results in Table 1, it can be seen that in Examples 1-3, by adding a small amount of homemade reactive compatibilizer and regulating the screw combination during the preparation process, the mechanical properties of the composite material are enhanced, while maintaining the antibacterial efficiency, the probability of contact with the silver ions in the antibacterial agent is reduced, and the prepared material will not change color. Compared with Examples 1-3, the content of compatibilizer in Comparative Example 1 is relatively high. Due to the high activity of silver ions in the antibacterial agent, the composite material changes color. Silane coupling agent was added in Comparative Example 2. Due to the high activity of silver ions, the coupling agent contains active amine groups (nitrogen), which react easily with silver ions at high temperatures, causing the material to change color. In Comparative Example 3, when the screw combination is set to 7 groups, the screw combination design is relatively strong, which increases the contact opportunity between the antibacterial agent and the compatibilizer, and reacts during high-temperature injection molding, resulting in discoloration.

[0052] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A temperature-resistant and antibacterial AS composite material, characterized in that: The composite material is prepared from the following raw materials in parts by weight: AS: 66.4 to 88.8 parts by weight, Glass fiber: 10 to 30 parts by weight, Compatibilizer: 0.4-0.8 parts by weight, Inorganic silver antibacterial agent: 0.4-0.8 parts by weight, Auxiliary agent: 0.3-2 parts by weight, The compatibilizer is a styrene-maleic anhydride-acrylonitrile copolymer, and the anhydride content of the compatibilizer is 14% to 20%; AS, glass fiber, compatibilizer, inorganic silver antibacterial agent and auxiliary agent are conveyed to a twin-screw extruder for granulation according to mass ratio, wherein the screw combination of the twin-screw extruder includes 3 to 5 groups of shear blocks, each group of shear blocks has 1 to 2 shear blocks, and the angle of the shear block is one or more of 30°, 45° or 60°.

2. The heat-resistant and antibacterial AS composite material according to claim 1, characterized in that: The silver ion solubility in the inorganic silver antibacterial agent is 1-2%, and the carrier of the silver ion is zirconium phosphate.

3. The heat-resistant and antibacterial AS composite material according to claim 1, characterized in that: The glass fiber is an alkali-free chopped glass fiber, the monofilament diameter of the glass fiber is 7 μm to 14 μm, and the fiber length is 3 mm to 4.5 mm.

4. The heat-resistant and antibacterial AS composite material according to claim 1, characterized in that: The auxiliary agent is one or more of an antioxidant, a lubricant, and a pigment.

5. The heat-resistant and antibacterial AS composite material according to claim 4, characterized in that: The antioxidant is one or more of a phenolic antioxidant or a phosphite antioxidant.

6. The heat-resistant and antibacterial AS composite material according to claim 4, characterized in that: The lubricant is ethylene bis stearamide or stearate.

7. The heat-resistant and antibacterial AS composite material according to claim 1, characterized in that: The preparation method of the styrene-maleic anhydride-acrylonitrile copolymer is as follows: maleic anhydride, styrene and acrylonitrile are stirred in the weight percentages of (10-20%): (70-85%): (5-10%) to form a solution, and the solution is added dropwise into styrene with a weight percentage of 20-25%, and the polymerization reaction is carried out in a normal pressure reactor at a temperature of 100-110° C. for 8.5-9.5 hours to obtain the styrene-maleic anhydride-acrylonitrile copolymer.

Citation Information

Patent Citations

  • Antibacterial glass fiber reinforced AS composition

    CN105504567A

  • Anti-jitter touch switch

    CN105742094A

  • Antibacterial mildew-proof reinforced ABS composite material for fan blades and preparation method thereof

    CN111500013A

  • Antibacterial reinforced AS composite material and preparation method thereof

    CN105462141A

  • Preparation method, product and application of nano-montmorillonite reinforced starch-based biodegradable film blowing material

    CN112405931A